Learning outcomes and perceptions of midwifery students about peer-teaching and lecture method in gynecology and infertility course - Mitra Safari; Behrouz Yazdanpanah; Saphora Hatamipour (Journal of Pedagogical Research, 2020)
This study was conducted to compare teaching gynecology and infertility courses with both lecture and peer methods. In 2018, a quasi-experimental study was designed at the midwifery department of a state university in Iran. A total of 32 midwifery students were participated in the study. During the first eight sessions, 50% of the course content was taught in the form of same-level peer - teaching. The last eight sessions of the course were taught by lecture. At the end of each session, students were given a post-test, also midterm and final exam. At the end of exams, each student was asked to complete a questionnaire assessing students' perception about teaching methods. The average mid- term exam score for peer - teaching (34.5 ± 5.5 ) was significantly (p<0.01 ) higher than the lecture method (30.4 ± 5.8 ), as well as average final exam score (7.2 ± 1.5  vs. 5.8 ± 1.6 ). The average overall student perception score for the peer - teaching method was significantly (p<0.01 ) higher than the corresponding score for the lecture method (86.8 ± 11.5  vs. 74.1 ± 12.4 ). Using the peer education as a complementary method in teaching theoretical courses along with the traditional lecture method seems to be appropriate.